Decolonising Qualitative Analysis: Collectively Weaving Understanding Using Talanoa and Fa’afaletui Pacific-Indigenous Research Methods - Mafile’o T; Vaka S; Leau K; Satele P; Alefaio-Tugia S (SAGE Publications, 2024)
Sense-making processes shape the messages and impacts of qualitative research. Using qualitative data analysis methods embedded within a Pacific-Indigenous research paradigm decolonises research. This article discusses the Pacific-Indigenous data analysis processes of talanoa and fa’afaletui employed within a study of Pacific elder care in Aotearoa New Zealand, conducted by scholars of Pacific/Moana heritage. While research literature has primarily identified talanoa and fa’afaletui as data collection methods, we discuss our use of talanoa and fa’afaletui as methods of analysis. Talanoa and fa’afaletui were engaged as collective processes of orality weaving understanding from the researchers’ lived experiences and navigating across languages. Enhancing authenticity and actionability are identified as benefits of talanoa and fa’afaletui collective data analysis. Considerations for implementing these methods are language, logistics and location.
Keywords: qualitative analysis; Pacific; Indigenous; research methods; talanoa; fa'afaletui; decolonising methodologies